Challenging the nexus: Integrating Western psychology and African cultural beliefs in South African mental health care - Letsoalo, Daniel Lesiba; Ally, Yaseen; Tsabedze, Wandile Fundo; Mapaling, Curwyn (PINS-Psychology in Society, 2024)
This article delves into the unique sociocultural landscape of mental healthcare in South Africa, spotlighting the divergent conceptualisations of mental illness inherent in African and Western cultures. While acknowledging certain similarities, it emphasises the importance of integrating African-centred perspectives into psychology’s training and practice. We contend that the prevailing focus on Western approaches to mental illness not only marginalises indigenous beliefs but also perpetuates the dominance of Western medical paradigms in healthcare systems. This trend risks pathologising the African experience of mental health and narrowing the understanding of African humanity through a lens of psychiatrisation and medicalisation. The article advocates for a more formal, integrative approach to mental healthcare that recognises and incorporates African notions of illness and health, underscoring the centrality of culture in the healing process. Our discourse calls for a paradigm shift towards an integrative model that respects and combines the strengths of both Western and African approaches to mental health, thereby fostering a culturally sensitive, inclusive, and effective mental healthcare system in South Africa.